1998
DOI: 10.1046/j.1432-1327.1998.2580061.x
|View full text |Cite
|
Sign up to set email alerts
|

β 2‐microglobulin can be refolded into a native state from ex vivo amyloid fibrils

Abstract: Ϫ EJB 98 0390/3 β2-microglobulin fibrils have been extracted from the femoral head of a patient who has been under chronic haemodialysis for 11 years. The primary structure of the N-terminal portion of the protein and mass determination by electrospray mass spectrometry demonstrate that β2-microglobulin, extracted as fibrils by the water extraction procedure, was not glycated and that Asn17 was not deamidated. Limited proteolysis was observed in more than 20% of β2-microglobulin molecules and the main cleavage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
102
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 110 publications
(107 citation statements)
references
References 23 publications
5
102
0
Order By: Relevance
“…This model might also represent a system for the evaluation of events, such as proteolysis, that could remodel, stabilize, or dissolve amyloid fibrils. We have clearly established that in natural amyloid fibrils, the full-length protein is the predominant species, but a form lacking the first six N-terminal residues (⌬N6␤ 2 -m) also exists (25,36). The remarkable amyloidogenic propensity of this species, in comparison with the full-length protein, and its ability to form fibrils at neutral pH is well documented (20,27).…”
Section: Discussionmentioning
confidence: 79%
“…This model might also represent a system for the evaluation of events, such as proteolysis, that could remodel, stabilize, or dissolve amyloid fibrils. We have clearly established that in natural amyloid fibrils, the full-length protein is the predominant species, but a form lacking the first six N-terminal residues (⌬N6␤ 2 -m) also exists (25,36). The remarkable amyloidogenic propensity of this species, in comparison with the full-length protein, and its ability to form fibrils at neutral pH is well documented (20,27).…”
Section: Discussionmentioning
confidence: 79%
“…Aggregates can form from the association of transient, partially folded intermediates during refolding experiments and during the production of recombinant proteins in heterologous expression systems (27) (28). For ␤ 2 -microglobulin, one of a group of 20 or so proteins associated with the formation amyloid fibrils in vivo (29), MS was used to identify N-terminally truncated forms of the protein present in high concentrations in ex vivo deposits (30). The H/D exchange properties of a mixture of wild-type and the major N-terminal truncation of ␤ 2 -microglobulin showed that the modified protein was significantly less protected from exchange than the wild-type protein (31).…”
Section: Protein Misfolding and Aggregationmentioning
confidence: 99%
“…Free ␤ 2 m then associates to form amyloid fibrils that typically accumulate in the musculoskeletal system and result in the development of the disorder dialysis-related amyloidosis. The majority of ex vivo ␤ 2 m amyloid is comprised of full-length wild-type ␤ 2 m, although small amounts (Ͻ30%) of modified or truncated forms are found (2)(3)(4).…”
mentioning
confidence: 99%